2001
DOI: 10.2116/analsci.17.1321
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Derivative Spectrophotometric Method for the Determination of Platinum in Pt-Ru/C Catalyst Using Iodide Media

Abstract: A rapid spectrophotometric method for the determination of platinum in 20% Pt-Ru (Pt:Ru (1:1)) carbon-supported catalyst has been developed. The samples of catalyst (0.85 -12.60 mg) have been digested 1) in aqua regia after preliminary separation of carbon by burning or 2) directly in aqua regia in the presence of carbon. The detection of platinum was carried out in the obtained solutions after conversion of the metal into the iodide complex. The interfering effect of ruthenium on the detection of platinum was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…[E] represents the catalyst concentration, K m is the Michaelis constant, V max is the maximal reaction velocity, and K cat is the catalytic constant that equals stable catalytic performance of the Ru frames might be attributed to their inherent inertness (e.g., ultrahigh resistance to oxidative etching) and the excellent thermal stability of elemental Ru (e.g., with an ultra-high melting point of [2,000°C) [28,38].…”
Section: Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…[E] represents the catalyst concentration, K m is the Michaelis constant, V max is the maximal reaction velocity, and K cat is the catalytic constant that equals stable catalytic performance of the Ru frames might be attributed to their inherent inertness (e.g., ultrahigh resistance to oxidative etching) and the excellent thermal stability of elemental Ru (e.g., with an ultra-high melting point of [2,000°C) [28,38].…”
Section: Catalystmentioning
confidence: 99%
“…Ru is quite unique compared to other noble metals. For example, Ru is chemically super stable and is even invulnerable to aqua regia [28]; Ru is the only noble metal that normally takes the hexagonal close-packed (hcp) crystal structure [29]. These unique features of Ru inspired us to explore Ru nanostructure-based peroxidase mimics.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the chemical stabilities of Ru and Pd are quite different . Specifically, Ru is highly resistant to oxidative corrosion and can hardly be dissolved by aqua regia . In contrast, Pd is much more vulnerable to chemical oxidation.…”
mentioning
confidence: 99%
“…44 Specifically, Ru is highly resistant to oxidative corrosion and can hardly be dissolved by aqua regia. 45 In contrast, Pd is much more vulnerable to chemical oxidation. On the basis of this difference in chemical stability, we chose chemical etching to selectively remove the Pd cores from the Pd−Ru core−frame octahedra.…”
mentioning
confidence: 99%
“…Spectrophotometric methods for the determination of platinum have been reviewed by Marczenko [6], who showed that various reagents have been used for the determination of platinum. Numerous spectrophotometric determinations of platinum(IV) have been reported with chromogenic reagents [7,8,9,10,11,12,13,14], but high selectivity reagents have been rarely reported. Other methods used for the determination of platinum include inductively coupled plasma atomic emission spectrophotometry [15], microwave oven-induced flowinjection analysis [16], and atomic emission spectrophotometry [17].…”
Section: Introductionmentioning
confidence: 99%